APPLICATION SLURRY AND BIO-SLURRY COW ON VARIOUS LEVEL TO GROWTH AND THE PRODUCTION OF FORAGE Stylosanthes guianensis - I P. C. A., Gunawan; Budiasa, I K. M.; Wirawan, I W. (Jurnal Peternakan Tropika, 2017)
This study aimed at obtaining information on the effect of using slurry and bio-slurry cow at various levels on the growth and production of forage Stylosanthes guianensis , which was conducted at Greenhouse in Banjar Sengguan-Pasekan, Sading Village, Mengwi sub-district, Badung Regency, Bali. The study was conducted for 10 weeks, using a complete randomized design (CRD) factorial pattern with two factors . The first faktor was the type fertilizer slurry cow (S), bio-slurry cow (B) and the second factor was level of fertilizer of 5 ton/ha (D1), 10 ton/ha (D2), 15 ton/ha (D3), 20 ton/ha (D4), 25 ton/ha (D5), 30 ton/ha (D6). So that there are 12 combination treatment repeated four times and there were 48 pot research. Variable observed growth, production and the characteristics. The results showed that there was a significantly affect  (P <0.05) between the fertilizer  type and the fertilizer level on the total dry weight of forage. Type of organic fertilizer slurry (S) significantly affect  (P<0,05) of leaf area. The fertilizer level significantly affected (P<0,05) the number of leaves, number of branch, leaf dry weight, dry weight of stem and total dry weight of forage. Based on the result of research can be concluded there was between type and level of slurry and bio-slurry cow organic fertilizer  of total dry weight of forage. Giving type of organic fertilizer slurry cow the highest being a kind of fertilizer bio-slurry cow of leaf area. The level of 25 ton/ha fertilizer gives the best result to growth and production of Stylosanthes guianensis. Keyword : Stylosanthes guianensis, slurry, bio-slurry, the levels fertilizer.